Determination of citric and oxalic acid in fungi fermentation broth through HPLC-DAD and solid-phase extraction - Laura Marcela Trujillo Vargas; Yesid Hernan Vélez Salazar; Margarita Enid Ramírez Carmona (Dyna, 2020)
This work describes a method for the simultaneous determination of organic acids in fungi fermentation broths. The sample preparation technique and the chromatographic conditions were optimized to enable the monitoring of the fermentation process. The determination of the citric and oxalic acid was done with a high resolution liquid chromatograph adapted to a detector with diode arrangement, an IC-Pak Ion-Exclusion 7μm (7.8 x 300 mm) column and a mobile phase of 0.001N H2SO4 with isocratic elusion. The validation parameters show efficiency, adequate linearity, and standard deviation values (%RSD) from 0.018% and 4.650%. the quantification limits (LDC) were 50.76 mg/L for citric acid and 20.18 mg/L for oxalic acid and the detection limits (LDD) were 0.6 mg/L for both acids. The method was applied in the analysis of organic acids in fermentation broths of Aspergillus niger.